Understanding speech and language in tuberous sclerosis complex - Gipson, Tanjala T.; Oller, D. Kimbrough; Messinger, Daniel S.; Perry, Lynn K. (Frontiers in Human Neuroscience, 2023)
Tuberous Sclerosis Complex (TSC), is a neurocutaneous disorder, associated with a high prevalence of autism spectrum disorder (ASD; ~50%). Understanding language development in TSC would not only be important for individuals with TSC but may also have implications for other causes of syndromic and idiopathic ASD. In this mini review, we consider what is known about language development in TSC and how speech and language are related to ASD. Although up to 70% with TSC report language difficulties, much of the research to date has been based on summary scores from standardized assessments. Missing is a detailed understanding of the mechanisms driving speech and language and how they relate to ASD. Here, we review recent work suggesting that canonical babbling and volubility—two precursors of language development that predict the emergence of speech and are delayed in infants with idiopathic ASD—are also delayed in infants with TSC. We then look to the literature on language development to identify other early precursors of language development that tend to be delayed in children with autism as a guide for future research in TSC. We argue that vocal turn-taking, shared attention, and fast mapping are skills that can provide important information about how speech and language develop in TSC and where potential delays come from. The overall goal of this research is to not only illuminate the trajectory of language in TSC with and without ASD, but to ultimately find strategies for earlier recognition and treatment of the pervasive language difficulties in this population.